PENERAPAN MODEL MIND MAPPING DALAM MENULIS PUISI PADA SISWA KELAS VIII SMP NEGERI 4 RAMBAH - Rita Arianti; Asih Ria Ningsih; Misra Nofrita (STKIP ROKANIA, 2021)
This research was motivated by the low value of writing poetry and the activities of students who were still of poor quality. This study aims to describe the improvement of student learning processes and results in writing poetry through themodel Mind Mapping. This type of research is classroom action research (Action Research). Analysis of the research data is qualitative and quantitative techniques. The results of this study are: (1) the application of the model Mind Mapping in writing poetry can increase student activity in learning, namely in the first cycle most of the student activities are in the fairly good category increasing in cycle II to be good. (2) The application of themodel Mind Mapping in poetry writing learning can improve the learning outcomes of SMP Negeri 4 Rambah class VIII students, namely in the pre-cycle class scores of 50,25 with 16,66 % ​​learning completeness, increasing in the first cycle obtaining class average scores became 76,30 with a percentage of completeness of 62,5 % and increased again in the second cycle obtained an average grade of 88,20 with a percentage of completeness of 95,83 %. Based on the results of the study it can be concluded that the application of the model Mind Mapping can improve the process and student learning outcomes in writing poetry on class VIII SMP Negeri 4 Rambah.